Situation-Aware TDMA Scheduling Algorithm for QoS Guarantee in Tactical Environments - Wi, Gwangjin; Nam, Sungchan; Ko, Young Bae; Park, Kyung Joon (Journal of Korean Institute of Communications and Information Sciences, 2022)
In the battlefield, it is important to share real-time information and respond immediately between the combat systems for completing a successful mission. Therefore, strict quality of service (QoS) requirements exist to ensure real-time transmission of tactical data in tactical sensor networks. Substantial studies on network resource management for QoS guarantees have been studied so far. However, it is difficult to apply the existing studies to tactical environments due to the uncertainty in tactical networks. In this paper, we propose a Time Division Multiple Access (TDMA) scheduling algorithm considering scenarios in which routing paths change in real-time due to link failure. By simulation using OPNET, we confirm that the proposed algorithm can guarantee the QoS requirements of tactical data while increasing energy efficiency.
Keywords: energy efficiency; period control; quality of service; tactical networks; time division multiple access